Synthesis of a dendritic cell-targeted self-assembled polymeric nanoparticle for selective delivery of mRNA vaccines to elicit enhanced immune responses - Fan, Chen-Yo; Wang, Szu-Wen; Chung, Cinya; Chen, Jia-Yan; Chang, Chia-Yen; Chen, Yu-Chen; Hsu, Tsui-Ling; Cheng, Ting-Jen R; Wong, Chi-Huey (Chemical science (Cambridge), 2024)
Recent development of SARS-CoV-2 spike mRNA vaccines to control the pandemic is a breakthrough in the field of vaccine development. mRNA vaccines are generally formulated with lipid nanoparticles (LNPs) which are composed of several lipids with specific ratios; however, they generally lack selective delivery. To develop a selective delivery method for mRNA vaccine formulation, we reported here the synthesis of polymeric nanoparticles (PNPs) composed of a guanidine copolymer containing zwitterionic groups and a dendritic cell (DC)-targeted aryl-trimannoside ligand for encapsulation and selective delivery of an mRNA to dendritic cells. A DC-targeted SARS-CoV-2 spike mRNA-PNP vaccine was shown to elicit a stronger protective immune response in mice compared to the traditional mRNA-LNP vaccine and those without the selective delivery design. It is anticipated that this technology is generally applicable to other mRNA vaccines for DC-targeted delivery with enhanced immune response. Dendritic cell-targeted mRNA-PNP vaccines.